Investigating Patient-Level Radiation Exposure in Hand and Wrist Fracture Surgery. (May 2022) - Xu, Wen; Christopher, Adrienne N.; Hu, Sophia; Steinberg, David R.; Bozentka, David J.; Lin, Ines C.
Abstract : Background: Although occupational exposure to radiation has been previously studied in the hand surgery literature, there is a paucity of studies looking at radiation exposure to the patient during fluoroscopy-guided hand surgery. We aimed to describe the level of radiation experienced by patients undergoing common hand and wrist fracture fixation and to identify risk factors for increased radiation exposure. Methods: We performed a retrospective review of patients at a single institution who underwent fracture fixation of the hand, wrist, or forearm requiring mini c-arm fluoroscopic guidance from 2016 to 2020. Data points collected included patient demographics, procedural details, and indicators of radiation exposure including dose-area product (DAP), total intraoperative images, and total fluoroscopy time. Effective dose (ED) was calculated using DAP, field size, and a previously established conversion factor. Results: The final sample included 361 patients with an average age of 46 years. Procedures included fixation of forearm fractures (3.3%), distal radius fractures (35.7%), metacarpal fractures (30.8%), and phalangeal fractures (30.2%). The median number of intraoperative images acquired was 36, median total fluoroscopy time was 43 seconds, median DAP was 4.8 cGycm 2, and median ED was 0.13 μSv. Distal (metacarpal and phalangeal) fractures required more intraoperative images and longer total fluoroscopy time (49 images, 61 seconds) compared with proximal (forearm and distal radius) fractures (39 images, 47 seconds) (images, P = 0.004; exposure time, P = 0.004). However, distal fractures had a lower average ED compared with proximal fractures (0.15 vs 0.19 μSv, P = 0.020). When compared with open procedures, percutaneous procedures had higher DAPs (8.8 vs 4.9 cGycm 2, P < 0.001), higher ED (0.22 vs 0.15 μSv, P < 0.001), more intraoperative images (65 vs 36 images, P < 0.001), and longer total fluoroscopy time (81.9 vs 44.4 seconds, P < 0.001). Conclusions: Patient-level radiation exposure during fluoroscopy-guided hand and wrist procedures is low relative to other common imaging modalities, such as dental radiographs, chest x-rays, and computed tomography scans, and is comparable with less than a few hours of natural background radiation exposure, highlighting the overall safety of this important technology. Further study should be performed to establish reference ranges, which could lead to improved patient counseling and evidence-based guidelines on patient shielding.